Contractors’ Perspective on the Main Factors Influencing On-Site Labour Productivity: A Focus on Malaysian Infrastructure Projects - Hanafi, Mohd Hanizun; Ong , Ming Zhen; Abdul Razak, Arman (International Journal of Sustainable Construction Engineering and Technology, 2021)
The overall performance of construction projects has been seemingly low and has negatively affected its efficacy in fulfilling national development agenda. Infrastructure projects are complex and riddled with numerous construction risks, and often involve large financial investments as well as several resources, particularly labour. The objective of this research paper is to identify the main factors that influence labour on construction sites of infrastructure projects. In achieving this research objective, 26 factors were extracted from literature and subsequently distributed for assessment by 355 identified respondents via a questionnaire-based survey. 63 respondents, representing a response rate of 17.75%, participated in returning completed questionnaires for further analysis. The main factors that influence onsite labour productivity were identified through the use of Relative Importance Index analysis. The three most significant factors identified were co-ordination between sub-contractors, labour skill and expertise within specific job scopes, and, availability of updated construction drawings at the project sites. Several other factors were also extracted through the analysis conducted on the garnered data. These factors will collectively be able to accord contractors a better comprehension of the influencing elements that either impinge or promote labour productivity. These findings are pertinent for construction firms in the efforts to progressively increase the level of labour productivity in the Malaysian construction sector, particularly within the parameters of infrastructure projects.